Influence of Work Values and Quality of Life on Self-Esteem of STEM Teachers in Public Schools - Lantayona, Aidin; Carreon, Hazel (Journal of Interdisciplinary Perspectives, 2025)
In an era where quality education is paramount, understanding the factors that empower and retain our most vital educators is crucial. This study examines the often-overlooked interplay between professional and personal well-being among STEM teachers, addressing a critical research gap: the specific influences on their well-being and retention in public schools, particularly how work values, quality of life, and self-esteem interact. This deficiency limits effective support strategies for these essential educators. This research investigated the relationship between work values, quality of life, and self-esteem among 300 permanent STEM teachers from Davao Oriental, selected through stratified random sampling. Findings revealed a very high overall level of work values (mean = 4.30), with self-esteem (4.44), self-realization (4.43), self-growth (4.40), social interaction (4.37), and security (4.36) rated highest, while health and transport (3.81) were rated lowest. These results emphasized that a supportive work environment is crucial for boosting self-esteem, aligning with Maslow's Hierarchy of Needs and Self-Determination Theory. The study concludes that fulfilling teachers' needs for autonomy, competence, and relatedness is vital for self-actualization. Therefore, school administrators should prioritize policies that promote professional development, financial security, and overall well-being to enhance STEM teachers' self-esteem and foster professional fulfillment, providing evidence-based insights for policy development.